2018
DOI: 10.2196/preprints.11973
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recommendations for Methodology of Virtual Reality Clinical Trials in Health Care by an International Working Group: Iterative Study (Preprint)

Abstract: Background: Therapeutic virtual reality (VR) has emerged as an efficacious treatment modality

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…This study showed the importance of thorough implementation. However, generally, the emphasis on systematic, multi-level implementation is lacking concerning VR's application in healthcare (Levac et al, 2015;Birckhead et al, 2019;Kouijzer et al, 2023). The current study provides valuable initial insights into important aspects of the introduction of VR technology into treatment practice.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…This study showed the importance of thorough implementation. However, generally, the emphasis on systematic, multi-level implementation is lacking concerning VR's application in healthcare (Levac et al, 2015;Birckhead et al, 2019;Kouijzer et al, 2023). The current study provides valuable initial insights into important aspects of the introduction of VR technology into treatment practice.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…Thus, users can be immersed in VR simulations and interact with virtual content for human performance measurement and training, and by extension for the clinical purposes of assessment and intervention. This "Ultimate Skinner Box" perspective makes VR technology well-matched to the requirements of various experimental and clinical objectives and this provides conceptual support for its use in a wide variety of healthcare contexts (Maples-Keller et al, 2017;Rizzo and Koenig, 2017;Birckhead et al,. 2019;Hoffman et al, 2019;Powers and Rothbaum, 2019;Riva et al, 2019;Slater et al, 2019;Schweitzer and Rizzo, 2022;Lacy et al, 2023;Rizzo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%